La reflexión creativa en el diálogo epistolar de N. V. Gogol y de V. A. Zhukovskij de la segunda mitad de los años 1980 - Boznak Оlga A. (Cuadernos de Rusística Española, 2012)
The paper analyzes NV Gogol’s and VA Zhukovsky’s epistolary dialogue, unfolded in connection with the publication of Gogol’s “Selected passages from correspondence with friends.” Particular attention is paid to methodological and gender aspects of creative reflection, its leading motives are noted and interpreted.